2022
DOI: 10.3389/fpsyt.2022.841097
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Poor Sleep Quality During the COVID-19 Pandemic Among Women Attending Antenatal Care Services at the Health Facilities of Debre Berhan Town, Ethiopia: An Institutional-Based Cross-Sectional Study

Abstract: BackgroundWomen’s ability to get sleep can be affected by pregnancy-related hormonal changes or other external stressful situations like the coronavirus disease 2019 (COVID-19).ObjectiveThe objective of this study was to assess the proportion of poor sleep quality during the COVID-19 pandemic and its determinants among pregnant women attending antenatal care (ANC) services.MethodsAn institutional-based cross-sectional study was conducted among 423 women attending ANC services at the health facilities in Debre … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 38 publications
2
11
1
Order By: Relevance
“…It is well established that household composition (i.e., family size, living with dependent children, having outdoor space) has played an important role in mental health in people during the lockdowns, affecting mood, sleep quality, and stress levels [53]. According to our results and the literature, multiparous women had a higher risk of insomnia and stress when compared with primiparous ones [54,55]. Likewise, we found that in addition to multiparity, advanced maternal age, months of puerperium, and living in the North region of Argentina were insomnia promoters, coinciding with the postpartum sleep determinants documented by Khadka et al [56].…”
Section: Discussionsupporting
confidence: 62%
“…It is well established that household composition (i.e., family size, living with dependent children, having outdoor space) has played an important role in mental health in people during the lockdowns, affecting mood, sleep quality, and stress levels [53]. According to our results and the literature, multiparous women had a higher risk of insomnia and stress when compared with primiparous ones [54,55]. Likewise, we found that in addition to multiparity, advanced maternal age, months of puerperium, and living in the North region of Argentina were insomnia promoters, coinciding with the postpartum sleep determinants documented by Khadka et al [56].…”
Section: Discussionsupporting
confidence: 62%
“…This study was conducted during the time the first wave of Covid-19 hit Ethiopia, so there are anxiety and fear of the pandemic, which in turn increase the magnitude of poor sleep quality. Furthermore, being locked down and inability to engage with friends and relatives due to Covid-19 restrictions could also rise the prevalence ( 41 44 ). In this study, more than half (51%) of the participants had depression, which is a known risk factor for poor sleep quality and could be another explanation for the observed high prevalence of poor sleep quality ( 45 , 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of poor sleep quality (PSQI global score of >5) was high among pregnant patients, with an observed increase in prevalence with the advancement of gestational age and maternal age. It ranged between 59.5% in Indonesian studies and 88% in Turkish studies [ 49 ]. In a meta-analysis, these numbers were reduced to a pooled prevalence of 13% [ 50 ].…”
Section: Prevalence Of Sleep Disturbances In Covid-19 Patientsmentioning
confidence: 99%